2021
DOI: 10.1093/mnras/stab1593
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical evolution of planetesimals in the primordial disc

Abstract: The Primordial Disk of small icy planetesimals, once located at 15–30 AU from the Sun, was disrupted by giant planet migration in the early Solar System. The Primordial Disk thereby became the source region of objects in the current–day Kuiper Belt, Scattered Disk, and Oort Cloud. I present the thermophysics code ‘Numerical Icy Minor Body evolUtion Simulator’, or NIMBUS, and use it to study the thermophysical evolution of planetesimals in the Primordial Disk prior to its disruption. Such modelling is mandatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 216 publications
3
46
0
Order By: Relevance
“…Figure 22). Moreover, thermal evolution models suggest that pure CO cannot survive long-term in comets (Davidsson 2021). Explanations attempting to match activity to the sublimation of less volatile, less abundant materials (such as H 2 S) struggle to provide a convincing match to the 8 to 10 au critical distance (Poston et al 2018).…”
Section: Centaursmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 22). Moreover, thermal evolution models suggest that pure CO cannot survive long-term in comets (Davidsson 2021). Explanations attempting to match activity to the sublimation of less volatile, less abundant materials (such as H 2 S) struggle to provide a convincing match to the 8 to 10 au critical distance (Poston et al 2018).…”
Section: Centaursmentioning
confidence: 99%
“…Establishing proof of the existence of amorphous ice in JFCs and Centaurs would be of great scientific value. It would imply that ice in the precursor Kuiper belt objects has also survived in the amorphous state, significantly limiting the post-accretion thermal processing of these bodies (see Davidsson 2021 and the chapter by Prialnik and Jewitt).…”
Section: Centaursmentioning
confidence: 99%
“…Indeed, Guilbert-Lepoutre (2012) found that crystallization of amorphous water ice can be a source of activity, efficient at heliocentric distances up to 10-12 au, sustained though for a limited time (typically hundreds to thousands of years). This implies that active Centaurs should have suffered a recent orbital change Davidsson (2021). nuanced this result, by showing that crystallization would be efficient only up to 8-10 au, while the sublimation of CO 2 would be the only source of activity in the 10-12 au region.…”
mentioning
confidence: 92%
“…Considerable modelling efforts have examined the possibility of thermal processing and activity even from the earlier stages of evolution. Such studies propose that alterations start as early as the formation of comet nuclei, and before their displacement in outer solar system reservoirs (e.g Prialnik & Merk 2008;Raymond et al 2020;Davidsson 2021), but also during the prolonged storage phase, where surface temperatures between 30 and 50 K can be attained (e.g. Capria et al 2000;De Sanctis et al 2000, 2001Choi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Combined, these two effects are known to regulate the near-surface temperature and therefore the activity of comets. In recent years, various studies have indeed looked at different aspects related to the surface of comets, that are associated with these thermal modifications (Hu et al 2019;Gundlach et al 2020;Davidsson 2021). However, much less is known about the role of pebble structure on the internal, long-term physical and thermal evolution of comets.…”
Section: Introductionmentioning
confidence: 99%